2011
DOI: 10.1089/pho.2010.2914
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Polarized Light (λ400–200 nm) on the Healing of Third-Degree Burns in Induced Diabetic and Nondiabetic Rats

Abstract: Our results suggest that the use of PL (10.2 J/cm(2)) improves the healing of third-degree burns on both diabetic and nondiabetic animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
(21 reference statements)
0
16
0
3
Order By: Relevance
“…Instrument heated until red and incandescent (11. 1%) [24,25] immersion in water at 95 °C (5.5%) [15], immersion in water at 100 °C (5.5%) [23], or cylindrical brass rod cooled to 77 K (5.5%) [21]. These find-ings suggested a good standardization between the experi-mental models of third-degree burns, allowing the reproduc-ibility of the experimental models (Table 1).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Instrument heated until red and incandescent (11. 1%) [24,25] immersion in water at 95 °C (5.5%) [15], immersion in water at 100 °C (5.5%) [23], or cylindrical brass rod cooled to 77 K (5.5%) [21]. These find-ings suggested a good standardization between the experi-mental models of third-degree burns, allowing the reproduc-ibility of the experimental models (Table 1).…”
Section: Resultsmentioning
confidence: 96%
“…Of these, 1164 were excluded for not meeting the inclusion criteria of this systematic review: repeated study (n = 5), in vitro study (n = 120), clinical study (n = 62), systematic review (n = 76), ab-stract only (n = 47), it is not of third-degree burn (n = 854). Finally, 17 studies [4,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] in which diverse treatment pa-rameters of injuries were assessed were included for critical evaluation of the effectiveness of PBMT in third-degree burn. The 17 selected studies totaled a sample of 845 animals and showed some common characteristics, namely the use of adult male Wistar rat with a mean weight of 278.5 g as an experimental model and the dorsal region of the animals as the region where burns were performed in all (100%) studies.…”
Section: Resultsmentioning
confidence: 99%
“…Além disso, os resultados da massa corporal dos animais desnutridos após 30 dias mostraram diferenças significativas (p = 0,0001) quanto aos nutridos. A gelatina apresenta ausência de triptofano, e com isso a conversão para niacina é diminuída, levando a supressão do crescimento [30,31]. Quanto à albumina sérica, que foram semelhantes entre os grupos, a ausência do triptofano na gelatina leva a uma supressão de niacina, sendo que o triptofano presente no organismo passa a ser utilizado na síntese de proteínas endógenas importantes (albumina).…”
Section: Discussionunclassified
“…São raros estudos que abordaram os efeitos da fototerapia em queimaduras em modelos patológicos. Alguns estudos mostraram efeitos positivos do laser em queimaduras em ratos normais e diabéticos [31,33], porém não há estudos em modelos de desnutrição.…”
Section: Figura 4 -Evolução Das Queimaduras Nos Grupos Experimentais unclassified
“…It is known that polarized light accelerates wound healing, but at present, there are single researches. They testify to high efficiency of application of visible range of electro-magnetic waves for burn wounds healing and rehabilitation of patients with burns [4,5]. Monstrey et al [6] reported statistically reliable acceleration of deep burns healing.…”
mentioning
confidence: 99%